Impact of TV content in social media. Case study: Ecuador [Impacto de los contenidos televisivos en medios sociales. Caso de estudio: Ecuador] - Suing Ruiz, A. (2016)
© 2016 AISTI.The rise of social media represents substantial changes in the configuration of television content in Ecuador. In this scenario concerns arise: How social networks are integrated in different types of content? Is the impact achieved at the hearing is similar in television and social media? The investigation seeks to establish through a quantitative methodology, trends in social media in relation to the content classification made by the Communications Law of Ecuador, to determine the impact of contents in television and social networks.